(untitled) (Journal of Social Sciences Review, 2023)
Basic aim of this systematic review paper is to overview the ergonomics risk factors associated with jobs and enumerate the associations between risk factors such as organizational, psychosocial, biomechanical, hard physical job risk factor and work-related musculoskeletal problems. PRISMA methodology for paper selection is adopted and selects 103 papers from springer and Elsevier, published during 2001 to 2021. Books and review papers are excluded from the review. Ergonomics risk factors of MPD issues such as palm pain, hand-wrist pain, arm pain, shoulder stretching and pain, neck pain, lower back pain, back bent, knee pain and foot pain among the workers of various industries. Out of 103 studies, link between WMPD and biomechanical risk factors is 30%, with psychosocial risk factors is 30%, with organizational risk factors is 26% and with physical job is 14%. As review indicates the association of ergonomic risk factors with work related MPD. There must be ergonomic interventions to overcome these MPD issues. Training and exercises must be guided to employees. Correct posture, sitting and standing positions to avoid associated job risk must be communicated to employees. There must be effective communication among employees and management to take an effective decision to resolve ergonomic risk factors associated with jobs.